NCTUns Emulation Testbed for Evaluating Real-life Applications over WiMAX Networks - Wang, Shie-Yuan; Lin, C. C.; Koo, P. H.; Huang, Y. M.; Yang, Jen-Shun (My University, 2010)
In this paper, we design and implement a hybrid WiMAX network testbed that integrates the NCTUns network emulator with a real-life WiMAX network. This hybrid WiMAX network testbed can seamlessly connect virtual networks (emulated by NCTUns) to a real-life WiMAX network. Thus, in this testbed real-life applications on real machines can exchange data with those on emulated (virtualized) network nodes. With this unique feature, our developed testbed provides a powerful, high-fidelity, and convenient testing environment for evaluating the performances and behaviors of real applications and devices in WiMAX networks. In this paper, the architecture and methodology of the developed testbed are explained, which are general and can collaborate with any other IP-based networks. In addition, an example study on this testbed is also presented to demonstrate its usage and capabilities.